About the Procedure of Background Checks for Candidates for Public Authority Positions - Khabarova, T. V. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article is devoted to the consideration of the procedural form of such anti-corruption measure as a special check of candidates for positions in public authorities. Оutlines the negative impact of corruption, which results in the introduction of a special verification of the relevant subjects, describes the four stages of the special check, and analyzes the actions of participants in this proceeding